Arm Dimensions of Patients with Obesity and Their Experiences with Blood Pressure Measurement: An Observational Study. Issue 4 (25th February 2020) - Ceglowski, Peter; Lehane, Katie; Chow, Christopher; Pelecanos, Anita; Tognolini, Angela; Eley, Victoria
Abstract : Objective: In patients with obesity, it was determined what proportion had an arm slant angle (SA) < 83° and which measure best predicted arm conicity. Patient experience with noninvasive blood pressure measurement was evaluated. Methods: Arm SA was calculated from arm measurements. Linear regression determined whether BMI, weight, or right midarm circumference (MAC) best predicted conicity. Patient experiences were evaluated by survey and conventional content analysis of free‐text comments. Results: One hundred participants had a median (interquartile range; range) BMI of 44.1 (39.1‐53.1; 31.1‐80.8). Thirty‐three (33%) had a right arm SA < 83°. Seven (7%) had a right MAC outside the recommended range. BMI, weight, and the right MAC showed low correlation with and explained little of the variation (with age and sex adjustment) in right arm SA (r = −0.29, −0.27, −0.31; P  = 0.003, 0.007, 0.002; R 2  = 0.09, 0.08, 0.10). Forty‐two (42%) reported noninvasive blood pressure measurement caused severe pain, and 30 (30%) reported skin damage. Themes identified in free‐text responses were "problems with equipment, " "feelings and experiences, " and "concerns about accuracy." Conclusions: Current equipment is inadequate for patients with obesity based on MAC and conicity. Pain and skin damage contributed to negative experiences of these patients.